Study of tension in the periodontal ligament using the finite elements method - Cossetin, Eliziane; da Nóbrega, Selma Hissae S.; de Carvalho, Maria Goretti Freire [UNESP] (FapUNIFESP (SciELO), 2012)
Orthodontic movement is process of transformation of a physical stimulation into a force applied to a tooth, with a biological response identified as bone remodelling. Although it is possible to measure the force applied on a tooth, its distribution around the root is irregular forming areas of higher concentration of tensions, which do not correspond to the force initially applied. To evaluate the behavior of the periodontal ligament after the application of an external action and to prove which would be the areas of higher tension generated in the periodontium, the Finite Elements Method (FEM) was used in comparison to the results obtained in vivo on experimental models in rat. To test the error susceptibility of the technique used in the experimental model, the force application was simulated in three different heights on the mesial surface of the molar. The resulting histological analysis was compared with the result obtained for the computational code and disclosed that the greater focus of osteoclasts in activity had coincided with the compressed areas of the periodontal ligament. The alteration of points of force application generated areas of more extensive deformations in the periodontal ligament, as the point of application was more distant of the initial point, the horizontal force vector became bigger. These results demonstrate that the FEM is an adequate tool to study the distribution of orthodontic forces. The sensitivity of the experimental model used was also observed in relation to the installation of the dental movement device, which should be considered depending on the objective of the research.
Keywords: Method of the finite elements; Orthodontics; Tensions